The School Climate - Student Achievement Connection: If We Want Achievement Gains, We Need to Begin by Improving the Climate (Journal of School Administration Research and Development, 2016)
This study examined the relationship between school climate and student achievement rat- ings in urban school districts in five states (N =230). Many educators view school climate and student achievement as separate considerations. However the results of this study suggest that climate and student achievement were highly related. In fact, the quality of the climate appears to be the single most predictive factor in any school’s capacity to promote student achievement. The findings of the study suggest a se- ries of general and theoretical implication for the field of education. It appears that the use of practices that promote a “psychology of success” lead to greater achievement and higher quality climate, and those that promote a “psychology of failure” lead to under- performance.